Estudo da métrica para análise de crédito: compra e venda de recebíveis - Bressiani, Dozoline (Universidade do Vale do Rio dos Sinos, 2013)
The activity of factoring is part of the Brazilian financial system, is a subsystem of intermediation and fits the technical name as the chart of the financial system as other banking institutions, non-banking and auxiliaries. The objective of this work is the study of a metric for the analysis of credit for factoring. Are used MS Project and WBS structure for the idea and steps of the study. For this work, it is the project plan comprising the steps seen in the classroom: scope statement, WBS and dictionary, Responsibility Matrix, Communication Plan, Quality Plan, Map acquisitions, Schedule, Budget and Management risks, control, credit analysis with a survey of their steps and finally the final considerations of the evaluation study on the feasibility of the project. This work was important to study a metric for credit analysis, since today the company in question, there is no formal process for this analysis.
Keywords: MS Project; WBS; Gestão de projetos; Métrica; Análise de crédito; Fomento mercantil; Project management; Metrics; Credit analysis; Factoring